Penerapan Standar Manajemen Mutu Berbasis Iso 9001:2015 PT. Dutabahari Menara Line Dockyard Banjarmasin - lidiana lidiana; Siti Noor Farida (Economy Deposit Journal (E-DJ), 2022)
This study aims to determine and explain the implementation of ISO 9001:2015 based quality management standards on PT. Dutabahari Menara Line Dockyard Banjarmasin. The method used in this research is descriptive method. Data obtained based on the results of interview, observation, and direct observation made by the author.The results of research conducted by the author can conclude that the application of quality management standards based on ISO 9001: 2015 at PT. Dutabahari Menara Line Dockyard Banjarmasin has been implemented passably. Although there are still principles that have not been met, the company is expected to be able to increase the support of various parties, in the end must be fulfilled.